Educational software and its impact on the learning process in university. (2020)
This chapter describes a study carried out in 2019 which evaluated the use of ICTs, specifically the LógicaUCAB educational software, and its effects on students’ learning of the Propositional Logic content from the Computing Logic course of the Computer Engineering degree of the Universidad Católica Andrés Bello (UCAB). Two groups of stu dents were selected: an experimental group, who used the LógicaU CAB tool in a laboratory during five weeks, one session per week, and a control group, which did not have access to the software. The official UCAB platform (Módulo7-Canvas) was also used for virtual activi ties. The research methodology was quasi-experimental, since groups were formed non-randomly. Finally, a written test was applied to both groups to verify results. These showed a positive effect on the academic performance of the students regarding the Propositional Logic content when using LógicaUCAB in the Computational Logic course. Based on this experience, a program that can be further applied and that con tributes to student learning of Propositional Logic is formally detailed, through the use of an Educational Software and some other ICT tools.